Effect of Omega-3 Eggs and Insoluble Dietary Fibre on the Physico Chemical, Proximate and Sensory Properties of Chicken Nuggets - Sathu, T; Joseph , Aaliya Tahseenand Rintu (Journal of Meat Science, 2023)
The study was aimed to select a suitable dietary insoluble fibre (DISF) for incorporating in functional chicken nuggets enriched with omega-3 eggs (OE). The wheat fibre (T1) and sorghum fibre (T2) at 4 per cent level were used separately as sources of DISF in the formulation and were evaluated for various physico-chemical characteristics, proximate composition and sensory properties and compared with control C1 (without any functional ingredients) and C2 (enriched with 7.5 per cent OE). The DISF enriched chicken nuggets differed significantly (P<0.05) from the control chicken nuggets with respect to emulsion pH, cooking yield, moisture, protein and fat content. The lightness and yellowness values were significantly higher for the T1 and T2 chicken nuggets but redness value was significantly lower for T1 and T2 than control C1. Wheat fibre at 4.0 per cent level lowered the sensory score values. Acceptable functional chicken nuggets can be made by incorporating 7.5 per cent OE and 4.0 per cent sorghum fibre without deteriorating the nutritive and sensory qualities of the product and was comparable with controls.